Which of the following expressions is not equivalent to the rest?(1 point)
m⋅1+7
17⋅m⋅7+7
18+m−11
5+m−12
5 answers
m⋅1+7 is not equivalent to the rest of the expressions.
Complete the following stepped-out solution to show that 15+g+32⋅23 is equivalent to 16+g.(1 point) 15+g+32⋅23 15+g+ Inverse Property of Multiplication 15++g Commutative Property of Addition 16+g Addition
15+g+32⋅23
= 15+g+ (32⋅23) (Inverse Property of Multiplication)
= 15+g+736 (Commutative Property of Addition)
= (15+736)+g (Associative Property of Addition)
= 751+g (Addition)
= 16+g (Simplified)
= 15+g+ (32⋅23) (Inverse Property of Multiplication)
= 15+g+736 (Commutative Property of Addition)
= (15+736)+g (Associative Property of Addition)
= 751+g (Addition)
= 16+g (Simplified)
Complete the following stepped-out solution to show that 15+g+3/2⋅2/3 is equivalent to 16+g.(1 point) 15+g+3/2⋅2/3 15+g+_ Inverse Property of Multiplication 15+_+g Commutative Property of Addition 16+g Addition
15+g+3/2⋅2/3
= 15+g+ (3/2⋅2/3) (Inverse Property of Multiplication)
= 15+g+ (3⋅2)/(2⋅3) (Simplified)
= 15+g+ 6/6 (Multiplication)
= 15+g+ 1 (Simplified)
= (15+1)+g (Associative Property of Addition)
= 16+g (Addition)
Therefore, 15+g+3/2⋅2/3 is equivalent to 16+g.
= 15+g+ (3/2⋅2/3) (Inverse Property of Multiplication)
= 15+g+ (3⋅2)/(2⋅3) (Simplified)
= 15+g+ 6/6 (Multiplication)
= 15+g+ 1 (Simplified)
= (15+1)+g (Associative Property of Addition)
= 16+g (Addition)
Therefore, 15+g+3/2⋅2/3 is equivalent to 16+g.